Precision agriculture: a contribution to agribusiness management from modeling - Cerón-Muñoz, Mario; Barrios, Dursun (Revista Colombiana de Ciencias Pecuarias, 2019)
New agriculture, new technologies? The incursion of new technologies is constantly changing the agricultural industry around the world. In fact, many technologies used in production systems are variations of: 1) “hard technologies” used in other sectors such as motoring, robotics, electronics, automation, and remote sensing and 2) “soft technologies” from social and political sciences, benchmarking and business. If the articulation of these technologies is achieved, the growth of the agricultural sector would be possible, seeking economic, environmental, productive, and social sustainability. Therefore, the concepts of precision agriculture, rural anthropology, and business management gain strength in production systems and their environment. The objective of this lecture is to show a look at agricultural sciences in front of the challenges of the 21st century, from the vision of the structural analysis of precision agriculture through the use of both hard and soft technologies without ignoring the role of “the human being” and “natural resources”.